Effects of visit-to-visit variability in systolic blood pressure on macrovascular and microvascular complications in patients with type 2 diabetes mellitus: the ADVANCE trial. - Hata, J; Arima, H; Rothwell, P; Woodward, M; Zoungas, S; Anderson, C; Patel, A; Neal, B; Glasziou, P; Hamet, P; Mancia, G; Poulter, N; et al. (2013)
BACKGROUND: Recent evidence suggests that visit-to-visit variability in systolic blood pressure (SBP) and maximum SBP are predictors of cardiovascular disease. However, it remains uncertain whether these parameters predict the risks of macrovascular and microvascular complications in patients with type 2 diabetes mellitus. METHODS AND RESULTS: The Action in Diabetes and Vascular Disease: Preterax and Diamicron Modified Release Controlled Evaluation (ADVANCE) was a factorial randomized controlled trial of blood pressure lowering and blood glucose control in patients with type 2 diabetes mellitus. The present analysis included 8811 patients without major macrovascular and microvascular events or death during the first 24 months after randomization. SBP variability (defined as standard deviation) and maximum SBP were determined during the first 24 months after randomization. During a median 2.4 years of follow-up from the 24-month visit, 407 major macrovascular (myocardial infarction, stroke, or cardiovascular death) and 476 microvascular (new or worsening nephropathy or retinopathy) events were observed. The association of major macrovascular and microvascular events with SBP variability was continuous even after adjustment for mean SBP and other confounding factors (both P<0.05 for trend). Hazard ratios (95% confidence intervals) for the highest tenth of SBP variability were 1.54 (0.99-2.39) for macrovascular events and 1.84 (1.19-2.84) for microvascular events in comparison with the lowest tenth. For maximum SBP, hazard ratios (95% confidence intervals) for the highest tenth were 3.64 (1.73-7.66) and 2.18 (1.04-4.58), respectively. CONCLUSION: Visit-to-visit variability in SBP and maximum SBP were independent risk factors for macrovascular and microvascular complications in type 2 diabetes mellitus. CLINICAL TRIAL REGISTRATION URL: http://www.clinicaltrials.gov.